2010
DOI: 10.1021/jf904119v
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hydrophobicity and Antioxidant Ability of “Phenolipids” in Emulsion: A Parabolic Effect of the Chain Length of Rosmarinate Esters

Abstract: The polar paradox predicts that hydrophobic antioxidants are more active in emulsions than their hydrophilic homologues, thus assuming a linear dependency between hydrophobicity and antioxidant capacity. In contrast, we formulate in this paper an alternative hypothesis assuming a possible nonlinear dependency. To verify this so-called "nonlinear hypothesis", the antioxidant capacity of a homologous series of rosmarinic acid and its alkyl esters (methyl, butyl, octyl, dodecyl, hexadecyl, octadecyl, and eicosyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
167
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(190 citation statements)
references
References 35 publications
21
167
2
Order By: Relevance
“…In vitro studies showed that the antioxidant capacity of RA alkyl derivatives could be higher than RA [32], and further work is in progress to more thoroughly characterize the methylated form of RA and to verify whether its production is a result of genuine biosynthesis or artifactual methylation during methanol extraction.…”
Section: Cads Quantificationmentioning
confidence: 99%
“…In vitro studies showed that the antioxidant capacity of RA alkyl derivatives could be higher than RA [32], and further work is in progress to more thoroughly characterize the methylated form of RA and to verify whether its production is a result of genuine biosynthesis or artifactual methylation during methanol extraction.…”
Section: Cads Quantificationmentioning
confidence: 99%
“…Thus, the results lead to the conclusion that lipophilization with medium chain fatty acids is a promising way to increase the antioxidant activity [16]. However, the results obtained with chlorogenate and rosmarinate esters have also led to the suggestion that the exact location of antioxidants in the discontinuous phase, interfacial layer or oil droplets, is important for the activity of the antioxidants [11,16]. In addition, a study on lipophilized dihydrocaffeic acids and their antioxidative effect in o/w emulsions reported by Sørensen et al [17] suggested that lipophilized dihydrocaffeic acid tended to follow the newly suggested cut-off effect in relation to the alkyl chain length attached although only two chain lengths were evaluated.…”
Section: Introductionmentioning
confidence: 95%
“…The current work in this area has been summarized by Shahidi and Zhong [15]. Laguerre et al [11,16] have recently reported on the antioxidative effect of lipohilized chlorogenic and rosmarinic acids. For chlorogenic acid the antioxidant capacity increased as the alkyl chain length was increased from 1 to 12 carbon atoms, whereas further increase of the chain length resulted in a drastic decrease in the antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, the lipophilization reactions are particularly advantageous and effective, and may be seen as a vectorization key unlocking the lipid barrier encountered by the bioactive molecule while maintaining its original functional properties. In the case of phenolic acids, the methods commonly used consists in attaching on the reactive carboxyl group, either a single or double tail lipophilic domain (usually an aliphatic with a different carbon backbone) resulting in new molecule with emulsifying properties, and often greatly improved antioxidant activity (Durand et al, 2015;Laguerre et al, 2010). This reaction can be performed on simple phenolic acids derived from benzoic acid (hydroxybenzoic acids), cinnamic (hydroxycinnamic acids) or more complex polyphenolic acids such as chlorogenic acid and rosmarinic acid with single or double tail (Fig.…”
Section: Lttm a New Family Of Promising Green Mediamentioning
confidence: 99%